Continuous Organic Characterization for Biological and Membrane Filter Performance Monitoring. Issue 4 (1st April 2017) - Peleato, NicolÁS M.; Legge, Raymond L.; Andrews, Robert C.
Abstract : Continuous organic characterization at a full‐scale drinking water treatment plant was achieved using fluorescence spectroscopy. The feasibility of this method was demonstrated through monitoring the performance of biological activated carbon contactors (BACCs), which serve as pretreatment for fouling control of ultrafiltration (UF) membranes. Fluorescence monitoring was applied successfully to identify the preferential removal of select fluorescence components and addition of another microbial humic‐like component by the biological filters. Spikes in BACC influent organic matter and fouling development on the downstream UF membranes highlighted the importance of preozonation. To demonstrate possible use of the short‐term continuous fluorescence data, neural networks were used to predict fouling development on downstream UF on the basis of BACC effluent water quality. Short‐term fluctuations in fouling development were well predicted by incorporation of continuous fluorescence characterization data. Continuous organic characterization shows promise for the application of fluorescence spectroscopy for real‐time process optimization and control in drinking water treatment systems.